RANCANG BANGUN SISTEM PENGENDALIAN INTENSITAS CAHAYA PADA SMART GREEN HOUSE UNTUK BUDIDAYA TANAMAN PAPRIKA MENGGUNAKAN FUZZY LOGIC - Marcia, Hadrian Wijaya; Nusantoro, Goegoes Dwi; Yudaningtyas, Erni (Jurnal Mahasiswa TEUB, 2024)
This study aims to design and evaluate a light intensity control system for a smart greenhouse using Fuzzy Logic to support the cultivation of paprika (Capsicumannuum). Paprika requires a specific light intensity of approximately 3500 lux for optimal growth; however, tropical conditions in Indonesia often result in excessive or fluctuating light intensity, hindering photosynthesis. The system was developed using a BH1750 sensor, ESP-32 microcontroller, AC Light Dimmer, and LED Grow Lights, integrated with ThingSpeak for real-time data monitoring. The control system utilized Mamdani Fuzzy Logic with the centroid defuzzification method. Testing was conducted under disturbance-free conditions and with external disturbances to assess system performance. The results demonstrated that the system effectively maintained the light intensity at the 3500 lux setpoint with a settling time of 120 seconds, a recovery time of 30 seconds, a steady-state error below 5%, and an overshoot of less than 10%. Additionally, the system adapted well to external disturbances, ensuring stable lighting conditions to meet the plants' needs. These findings highlight the effectiveness of Fuzzy Logic in automated light control for smart greenhouses, providing an optimal environment for paprikacultivationIndex Terms— Smart greenhouse, Fuzzy Logic, Paprika, Light Control, BH1750, ESP-32, LED Grow Lights, Thing Speak